Association of family doctor concept's implementation on doctor-patient interaction, perceived quality of care and glycaemic control among type 2 diabetes mellitus patients in primary health clinics in Kelantan - Nordin, Noorfariza (2020)
Background: Glycaemic control among patients with Type 2 Diabetes Mellitus (T2DM) was still low despite various strategies taken to improve it. The implementation of Family Doctor Concept (FDC) in providing ‘One Family One Doctor’ healthcare service was expected to escalate the improvement in the patient’s satisfaction towards doctor-patient interaction, quality of care, and outcome among T2DM patients. Objectives: The objectives of this study were to compare the satisfaction level of doctor-patient interaction, perceived quality of care and mean HbA1c between T2DM patients who attended FDC and non-FDC clinics in Kelantan, to determine the factors associated with good glycaemic control among T2DM patients attended FDC clinics in Kelantan, and to examine the relationship between mean HbA1c with doctor-patient interaction and the patient’s perceived quality of care in FDC and non-FDC clinics in Kelantan, accounting for patient-level characteristics, clinic-level characteristics and nesting of patients within clinics. Methodology: A cross-sectional study was conducted at primary health clinics throughout ten districts in Kelantan from February until May 2019 using the validated interview-guided Skala Kepuasan Interaksi Perubatan-11 (SKIP-11) questionnaire, the Patient Assessment of Chronic Illness Care (PACIC-M) questionnaire (Malay version) and proforma checklist. Chi-square test used to determine the difference in doctor-patient interaction satisfaction between patients attended both type of clinics, meanwhile independent t-test used to determine the difference in perceived quality of care and mean HbA1c. Multiple logistic regression used to determine the factors associated with good glycaemic control among FDC clinic’s attendees. Linear multilevel regression and multiple linear regression analysis were used to explore the relationship between mean HbA1c with doctor-patient interaction and the patient’s perceived quality of care. Result: Twenty primary health clinics involved. A total of 785 participants were recruited with response rate of 99.0%, and data from 772 participants were analysed . The FDC clinics attendees have higher proportion of doctor-patient interaction satisfaction compared to non-FDC attendees (40.1% vs. 33.7%, p= 0.070). The was no difference in perceived quality of care between both type of clinics attendees (p=0.806). T2DM patients attended FDC clinics has lower mean HbA1c as compared to non-FDC clinics attendees (p=0.046). Multiple logistic regression found that male (Adj. OR 2.56; 95% CI: 1.49,4.42; p=0.001) and single/widower (Adj. OR 2.35; 95% CI: 1.32,4.18; p=0.004) associated with higher odd for good glycaemic control. An increase in duration of diabetes (Adj. OR 0.93; 95% CI: 0.88,0.99; p=0.017), higher average T2DM patients attended clinic per day (Adj. OR 0.96; 95% CI: 0.93,0.99; p=0.007), and higher PACIC-M domain ‘follow-up/coordination’ (Adj. OR 0.70; 95% CI: 0.51,0.95; p=0.021) were associated with reduce odd for good glycaemic control among FDC clinics attendees. The multilevel analysis found that 2% of the variation in mean HbA1c was contributed by the clinic-level differences. The variability in mean HbA1c that could be explained by the combined doctor-patient interaction satisfaction and perceived quality of care was 14.2%. A one-unit increase in SKIP-11 score has 0.08 unit lower HbA1c (Adj. β: -0.08; 95% CI: -0.11,-0.06; p<0.001), a one-unit increase in PACIC-M score would has 0.46 unit higher HbA1c (Adj. β: 0.46 ; 95% CI: 0.14,0.77; p<0.005), and the type of clinic has no significant relationship towards mean HbA1c (Adj. β -0.48; 95% CI: -1.09,0.13; p=0.120). Conclusion: The strengthening of FDC in primary health care through improvement in doctor-patient interaction satisfaction and better coordinated care are essential to escalate good glycaemic control among T2DM patients in Kelantan.